Towards A Passion Economy - Prabhat Sunil Mhaske (IJRDO - Journal of Social Science and Humanities Research, 2025)
Introduction- New era of economy has attracted whole world. Additionally recent Covid-19 Pandemic had contributed lot in it. The traditional ways of earning and job has shifted in opposite direction . Gig economy is coming towards edge where new economy in the form of Passion economy is knocking the door of worlds market. In short, world is rapidly moving towards Passion economy where everyone will remember the Peter Ferdinand Drucker theory of modern economics. A passion economy allows individuals to scale their businesses exponentially, to work when and where they want, and to earn income passively. The concept of a passion economy includes a multi-faceted change in philosophy for creators, consumers and platforms. These changes include a focus on the needs of individual creators, the bridge between providers and consumers, and the ways platforms or marketplaces monetize and moderate the exchange of goods. The term passion economy is similar to and sometimes used interchangeably with the creator economy, where individuals build their own business brands online, are focused on their passion for working on projects they are interested in, and demonstrate their individual skillsets. (1) Since the pandemic started, more and more people have jumped onto the passion economy train. The premise is simple: you can make a living off your passions with the help of a digital platform. (2)